Integrated consensus genetic map and genomic scaffold re-ordering of oil palm (Elaeis guineensis) genome. (February 2023) - Mohd Sanusi, Nik Shazana Nik; Rosli, Rozana; Chan, Kuang-Lim; Halim, Mohd Amin Ab; Ting, Ngoot-Chin; Singh, Rajinder; Low, Eng-Ti Leslie
Abstract: A high-quality reference genome is an important resource that can help decipher the genetic basis of traits in combination with linkage or association analyses. The publicly available oil palm draft genome sequence of AVROS pisifera (EG5) accounts for 1.535 Gb of the 1.8 Gb oil palm genome. However, the assemblies are fragmented, and the earlier assembly only had 43% of the sequences placed on pseudo-chromosomes. By integrating a number of SNP and SSR-based genetic maps, a consensus map (AM_EG5.1), comprising of 828.243 Mb genomic scaffolds anchored to 16 pseudo-chromosomes, was generated. This accounted for 54% of the genome assembly, which is a significant improvement to the original assembly. The total length of N50 scaffolds anchored to the pseudo-chromosomes increased by ∼18% compared to the previous assembly. A total of 139 quantitative trait loci for agronomically important quantitative traits, sourced from literature, were successfully mapped on the new pseudo-chromosomes. The improved assembly could also be used as a reference to identify potential errors in placement of specific markers in the linkage groups of the genetic maps used to assemble the consensus map. The 3422 unique markers from five genetic maps, anchored to the pseudo-chromosomes of AM_EG5.1, are an important resource that can be used preferentially to either construct new maps or fill gaps in existing genetic maps. Synteny analysis further revealed that the AM_EG5.1 had high collinearity with the date palm genome cultivar 'Barhee BC4' and shared most of its segmental duplications. This improved chromosomal-level genome is a valuable resource for genetic research in oil palm. Graphical Abstract: ga1 Highlights: The oil palm pseudo-chromosomes contain ∼828 Mb (54%) of the assembly, ∼26% more bases compared to the published EG5-build. The orientations of 220 scaffolds representing ∼75% of the nucleotides in the pseudo-chromosomes were established. The pseudo-chromosomes contained ∼83.8% of the high-quality gene models. A total of 139 QTLs for important traits, sourced from literature, were successfully mapped onto the new pseudo-chromosomes. The 3422 unique markers anchored onto the genome sequence will become an important resource for genetic map construction.